Shape memory textile composites with multi-mode actuations for soft morphing skins. (1st October 2020) - Han, Min-Woo; Kim, Min-Soo; Ahn, Sung-Hoon
Abstract: Natural creatures morph their soft skins to adapt to the surrounding environments. Such unique morphing could be of great utility when creating bio-inspired soft robots. Here, we design shape memory textiles that may be used to create soft morphing shells woven using various kinds of fibers, including shape memory alloy wires. We explore the effects of fiber configurations, textile orientations, and lamination numbers in terms of actuation behaviors (deflections and blocking forces). Finally, soft morphing shells prepared from multiple laminates of shape memory textiles were created to allow three-dimensional surface morphing using two-dimensional laminated composites.